Two-dimensional warranty period optimization considering the trade-off between warranty cost and boosted demand. (April 2019) - Zhang, Zhaomin; He, Shuguang; He, Zhen; Dai, Anshu
Highlights: The trade-off between boosted demand and cost is considered in 2D warranty design. Demand based on attractiveness index is used to describe the boosted sales volume. A profit model is proposed to estimate the manufacturer's expected profit. The optimal 2D base warranty periods for three different cases are derived. Effects of different usage rates of customers in 2D warranty are considered. Abstract: Product warranty in the market has a significant role in both protection and promotion. The manufacturer faces a problem of optimizing the warranty period considering a trade-off between the warranty cost and marketing competition. Meanwhile, for a two-dimensional (2D) warranty, customers with different usage rates have various perceptions on warranty period. Based on the relationships between nominal usage rate and customer's usage rates, three different cases of designed 2D warranty period are discussed. Considering the variations in customers perceptions, a demand function based on attractiveness index is proposed to describe the boosted sales volume. Meanwhile, the expected warranty cost of 2D warranty based on a bivariate approach is derived when the product failures are minimally repaired. A profit model is developed to estimate the manufacturer's expected profit of providing a longer warranty period. The optimal extension of 2D base warranty period is obtained by maximizing the manufacturer's expected profit. Numerical examples in the automobile market are also conducted to validate the proposed model.